SADD ADZ-DZARI’AH SEBAGAI TINDAKAN PREVENTIF: ANALISIS PRAKTIK MAHAR MENGGUNAKAN UANG KERTAS YANG TIDAK LAGI BEREDAR DI INDONESIA - Niswah Nafiah; Muhammad Julijanto (LPPM STAI Muhammadiyah Probolinggo, 2026)
The phenomenon of giving a dowry including small denominations or antique money is common in society, such as in Delingan Village, Karanganyar District, but is hampered by the availability of some that are no longer in circulation and are simply stored and cannot be used. This practice has the potential to deviate from the principles of Islamic law, especially regarding benefit, simplicity, and the prohibition of waste. This study aims to analyze the dowry from an Islamic legal perspective, using the concept of sadd adz-dzari’ah as an effort to prevent the harm that arises from this practice. This study uses a qualitative research design with an empirical approach. Data collection through unstructured interviews and documentation. Data analysis includes data reduction, data presentation, and verification. The results of the study in the analysis of motifs (al-baits) create an impression of uniqueness, aesthetic beauty, and a reminder of the sacred time of marriage. The maslahah aspect represents emotional reinforcement of happiness, but more dominant is the mafsadah in the form of difficulty in finding ancient money, loss of usefulness (ancient money is only stored and cannot be used for transactions), potential waste of exchanging useful cash for useless assets, and violation of the principle of simplicity. The motive of giving a dowry by following trends also gives rise to subtle mafsadah that has the potential to shift the value of the dowry from a symbol of sincerity to an arena for aesthetic proof, making the tendency to judge a dowry from its attractive appearance